2020
DOI: 10.1101/2020.07.22.215707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wing musculature reconstruction in extinct flightless auks (PinguinusandMancalla) reveals incomplete convergence with penguins (Spheniscidae) due to differing ancestral states

Abstract: Despite longstanding interest in convergent evolution, factors that result in deviations from fully convergent phenotypes remain poorly understood. In birds, the evolution of flightless wing-propelled diving has emerged as a classic example of convergence, having arisen in disparate lineages including penguins (Sphenisciformes) and auks (Pan-Alcidae, Charadriiformes). Nevertheless, little is known about the functional anatomy of the wings of flightless auks because all such taxa are extinct, and their morpholo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 126 publications
1
8
0
Order By: Relevance
“…Recent studies have demonstrated that incomplete convergence may be especially common (Losos 2011;Kaeuffer et al 2012;Moen et al 2016), even among "classic" examples of convergence such as flightless birds (Watanabe et al 2020) and hypercarnivores (Meloro et al 2015). Gliders provide further evidence for this conclusion.…”
Section: Landscapementioning
confidence: 87%
See 1 more Smart Citation
“…Recent studies have demonstrated that incomplete convergence may be especially common (Losos 2011;Kaeuffer et al 2012;Moen et al 2016), even among "classic" examples of convergence such as flightless birds (Watanabe et al 2020) and hypercarnivores (Meloro et al 2015). Gliders provide further evidence for this conclusion.…”
Section: Landscapementioning
confidence: 87%
“…2016), even among “classic” examples of convergence such as flightless birds (Watanabe et al. 2020) and hypercarnivores (Meloro et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While these changes in flight muscle insertion may be apomorphic in dippers, that changes in muscular insertions occur after an increase in the relative mass of the flight muscles merits further investigation as pattern general to the evolution of WPD. Notable associated myological and osteological differences have been documented between flightless auks and penguins (Smith & Clarke, 2015; Watanabe et al, 2020), but myological comparisons of volant WPD birds remain to be made.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of integument (e.g., feather density, relative length of primaries and rectrices, narial coverings), the relative size of external nares as well as differences in levels of subcutaneous fatty tissues and relative size of integumentary glands were assessed. Special consideration was also given to the primary flight musculature (m. pectoralis and m. supracoracoideus) as both of these muscles provide thrust during WPD (Kozlova, 1961;Watanabe et al, 2020). The following formalin-preserved and skinned specimens were also evaluated: C. mexicanus (USNM 530549, 196710) Early shifts in integument preceding musculoskeletal shifts have been reported in the penguin stem lineage and some shifts in wing feathering even precede loss of flight in waterbirds (Clarke et al, 2010;Wang & Clarke, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation